Optimal Planning of On-Grid Hybrid Microgrid for Remote Island Using HOMER Software, Kish in Iran - Saeedeh Ebrahimi; Mehdi Jahangiri; Heidar Ali Raiesi; Afrooz Rahimi Ariae (International Journal of Energetica)
HOMER software functions as a tool for modeling and optimization of an energy generation micropower system based on renewable technologies. In this paper for the first time the monthly real load data have been used in HOMER to design a renewable-based microgrid in grid-connected mode for Kish Island, Iran. The calculations were performed in a way that the designed system could supply the load demand of the studied area with the lowest cost, least pollution, and highest reliability. To overcome the intermittency of renewable energy sources such as wind and solar, a combination of these sources in a hybrid system and installation of battery storage systems were considered. The solar radiation and wind speed data required by the software were obtained from the country’s meteorology and NASA website and used in the software. The analysis results of four scenarios, including national grid/diesel generator, national grid/diesel generator/solar cell, national grid/diesel generator/wind turbine, and national grid/diesel generator/solar cell/wind turbine, showed the prices per kWh of $0.483, $0.505, $0.472, $0.537, respectively. In these scenarios, the share of renewable energies was 0%, 8%, 11%, and 26%, respectively. The highest amount of electricity sold to the national grid was 1597095 kWh/y for the fourth scenario which had also the lowest rate of CO2 emissions by 4128650 kg/y.